Edmondo Rossoni and Tresigallo: An Atypical Case of a Regime Town - Brugnatti, Davide; Muroni, Giuseppe (Ex Novo: Journal of Archaeology, 2021)
In the last 30 years, the town of Tresigallo has to come to terms with the legacy of its dissonant heritage. The rediscovery of its history happened gradually. It began in 1985 with the organization of conferences that encouraged a public debate about its founder Edmondo Rossoni, a minister during the fascist era, and the buildings he commissioned in Tresigallo. The town’s historical and architectural value, in that its unique identity in relationship with a denied past, had to be first recognized at a community level. Public administration’s take-over has not always granted the protection of these rationalist structures: some demolitions happened even in the early 2000s. Between late 1980s and 2000s, an increasing number of architects, local historians, photographers, and artists became interested in the town’s history due to its almost wholly preserved 1930s architectural and urban features. Restoration works and raising research on rationalist architecture have pointed out that the town should be considered a cultural asset to be preserved and valued. This paper examines some urban regeneration projects undertaken by the public administration, such as the former G.I.L. (Gioventù Italiana del Littorio) being converted into a public library and Public Baths made into an exhibition space. It also investigates the touristic and cultural development of the territory through the organization of cultural events and the use of social media.